2009
DOI: 10.1073/pnas.0907262106
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous nitric oxide regulates the recovery of the radiation-resistant bacterium Deinococcus radiodurans from exposure to UV light

Abstract: Deinococcus radiodurans (Dr) withstands desiccation, reactive oxygen species, and doses of radiation that would be lethal to most organisms. Deletion of a gene encoding a homolog of mammalian nitric oxide synthase (NOS) severely compromises the recovery of Dr from ultraviolet (UV) radiation damage. The ⌬nos defect can be complemented with recombinant NOS, rescued by exogenous nitric oxide (NO) and mimicked in the wild-type strain with an NO scavenging compound. UV radiation induces both upregulation of the nos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 51 publications
1
66
0
3
Order By: Relevance
“…As a result, several hypotheses about NOS biological activity are still competing. Among them, bacterial NOSs could intervene in the survival and virulence of some pathogenic bacteria [236,240,241], in their recovery after oxidative damages [242], in detoxification processes [243] or in the biosynthesis of toxins [226,235,[244][245][246]. In this puzzling picture, the elucidation of the molecular mechanism might provide a new reading frame for the catalytic functionning and the biological activity of these numerous NOSlike proteins.…”
Section: Discussionmentioning
confidence: 98%
“…As a result, several hypotheses about NOS biological activity are still competing. Among them, bacterial NOSs could intervene in the survival and virulence of some pathogenic bacteria [236,240,241], in their recovery after oxidative damages [242], in detoxification processes [243] or in the biosynthesis of toxins [226,235,[244][245][246]. In this puzzling picture, the elucidation of the molecular mechanism might provide a new reading frame for the catalytic functionning and the biological activity of these numerous NOSlike proteins.…”
Section: Discussionmentioning
confidence: 98%
“…Following different hypotheses, Nudler and colleagues (22)(23)(24) proposed that bacNOSs could intervene in a series of functions related to host-pathogen interaction such as protection against oxidative stress (22), pathogen survival and virulence (23), or defense against antibiotics (24). Recently, Crane suggested that D. radiodurans NOS could intervene in the recovery processes of bacteria subject to a UV stress (25). Because NO production is primarily used by the host as a bactericidal weapon, we feel that NO is not the most appropriate molecule to elicit a concerted response against the host immune system.…”
mentioning
confidence: 99%
“…1). CuFL1 has been used to monitor NO production in bacterial cell cultures with great success (14,15), but to improve its applicability a cell-trappable version of the ligand is required. Cell-trappability is a key feature for biological experiments in intact tissues for which continual perfusion of tissue slices with artificial physiological saline solution is required.…”
mentioning
confidence: 99%